2021
DOI: 10.1177/2327857921101117
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Psychosocial Support Provided by an Augmented Reality Device for Children With Type 1 Diabetes

Abstract: Type 1 diabetes (T1D), previously known as juvenile diabetes, has a large impact on everyday life and can pose a number of challenges for both children and their parents. A patient-centered design company, Sproutel, has designed and developed Jerry the Bear®—an interactive augmented reality (AR) stuffed animal toy bear designed to provide children with T1D with comfort and education about their diabetes management through play. We evaluated the AR device in a research study that involved participation over the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…After examining the survey presented in Table S14 in Multimedia Appendix 2 [ 13 , 16 , 18 , 19 , 21 , 24 - 31 , 33 , 42 , 43 , 50 - 65 ], it was observed that all games, except Packy & Marlon [ 16 ], lacked clinical validation. Furthermore, assessing adherence was not a focus in any of the games.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…After examining the survey presented in Table S14 in Multimedia Appendix 2 [ 13 , 16 , 18 , 19 , 21 , 24 - 31 , 33 , 42 , 43 , 50 - 65 ], it was observed that all games, except Packy & Marlon [ 16 ], lacked clinical validation. Furthermore, assessing adherence was not a focus in any of the games.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, of the 18 games, 3 (17%) were previously available on Nintendo or mobile game stores, but currently only 2 (11%; MyDiabetic and Jerry the Bear) are available for download on mobile game stores. Most games were developed as prototypes or concept studies as part of academic projects, with only a few aimed at preschool children [ 50 - 52 ]. Only 1 (6%) of the 18 games addresses both basic (carbohydrate counting, blood glucose–level measurement, and insulin administration) and advanced (CGM and insulin pump) educational self-management skills [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As AR applications grow in popularity and their use expands to areas such as personal health information, there is a pressing need to evaluate AR systems "in the wild" (Rogers and Marshall, 2017) often remotely (Otiono et al, 2021). Conducting remote AR studies has the potential to reduce bias, increase generalizability, lower barriers to participant recruitment, and facilitate robust studies and analysis methods that require large sample sizes (Pratap et al, 2020;Ullman et al, 2021). While prior research has found remote study findings to be similar to the in-lab studies (Tullis et al, 2002;Nussenbaum et al, 2020), other challenges regarding remote studies persist.…”
Section: Introductionmentioning
confidence: 99%